Targeting Kaposi’s sarcoma associated herpesvirus encoded protease (ORF17) by a lysophosphatidic acid molecule for treating KSHV associated diseases - Rafeeq, Misbahuddin M; Habib, Alaa Hamed; Nahhas, Alaa F.; Binothman, Najat; Aljadani, Majidah; Almulhim, Jawaher; Sain, Ziaullah M; Alam, Mohammad Zubair; Alturki, Norah A; Alam, Qamre; Manish, Manish; Singh, Rajnish Kumar (Frontiers in Cell and Developmental Biology, 2023)
Kaposi’s sarcoma associated herpesvirus (KSHV) is causative agent of Kaposi’s sarcoma, Multicentric Castleman Disease and Pleural effusion lymphoma. KSHV-encoded ORF17 encodes a protease which cleaves -Ala-Ala-, -Ala-Ser- or -Ala-Thr- bonds. The protease plays an important role in assembly and maturation of new infective virions. In the present study, we investigated expression pattern of KSHV-encoded protease during physiologically allowed as well as chemically induced reactivation condition. The results showed a direct and proportionate relationship between ORF17 expression with reactivation time. We employed virtual screening on a large database of natural products to identify an inhibitor of ORF17 for its plausible targeting and restricting KSHV assembly/maturation. A library of 307814 compounds of biological origin (A total 481799 structures) has been used as a screen library. 1-oleoyl-2-hydroxy-sn-glycero-3-phospho-(1’-myo-inositol) was highly effective against ORF17 in in-vitro experiments. The screened compound was tested for the cytotoxic effect and potential for inhibiting KSHV production upon induced reactivation by hypoxia, TPA and butyric acid. Treatment of reactivated KSHV-positive cells with 1-oleoyl-2-hydroxy-sn-glycero-3-phospho-(1’-myo-inositol) resulted in significant reduction in the production of KSHV. The study identified a lysophosphatidic acid molecule for alternate strategy to inhibit KSHV-encoded protease and target KSHV associated malignancies.